Chemical Stability of Sputter Deposited Silver Thin Films - Depla, Diederik (Coatings (Basel), 2022)
Silver films with a thickness below 50 nanometer were deposited on glass using DC magnetron sputtering. The chemical stability of the films was investigated by exposure of the film to a droplet of a HCl solution in a humid atmosphere. The affected area was monitored with a digital microscope. The affected area increases approximately linearly with time which points to a diffusive mechanism. The slope of the area versus time plot, or the diffusivity, was measured as a function of the acid concentration, the presence of an aluminum seed layer, and film thickness. The diffusivity scales linearly with the acid concentration. It is shown that the diffusivity for Al-seeded Ag films is much lower. The behavior as function of the film thickness is more complex as it shows a maximum.